The Thursday murder club - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club, 2020)
"In a peaceful retirement village, four unlikely friends meet weekly in the Jigsaw Room to discuss unsolved crimes; together they call themselves The Thursday Murder Club"--